Study of Sebuku River Water Quality and Public Perception of PT ABC's Mining Activities - Mujiono, Mujiono; Sastranegara, Moh. Husein; Effendi, Mukhtar (Journal La Lifesci, 2025)
The Sebuku River has an important role for the life of flora, fauna, and local communities in Nunukan Regency, North Kalimantan Province. Mining activities in this area raise concerns about potential water pollution. This study aimed to evaluate the impact of mining activities on the water quality of the Sebuku River. Sampling was carried out by purposive sampling at five observation stations between ST-1 and ST-5 based on predetermined coordinate points. The parameters tested included temperature, TSS, pH, DO, BOD, COD, NO₃, PO₄, CN⁻, and fecal coliform. The analysis method referred to SNI and the results are compared with class II river water quality standards in Appendix VI of Government Regulation of the Republic of Indonesia Number 22 of 2021. The results of the analysis showed that the TSS level of all stations exceeded the quality standard as the majority of respondents who stated that it was cloudy, but the level tended to decrease downstream. The highest COD parameters were detected in ST-2. This is supported by the value of the Pollution Index (PI) that indicated it as the primary pollution source from mining activities. The rest of the parameters are still within the permissible limits. Overall, the water quality of the Sebuku River is still classified as moderate based on the value of the Water Quality Index (WQI).